The acting person and Christian moral life - Weaver, Darlene Fozard (Moral traditions series., 2011)
What may we say about the significance of particular moral actions for one's relationship with God? In this provocative analysis of contemporary Catholic moral theology Darlene Fozard Weaver shows the person as a moral agent acting in relation to God. Using an overarching theological context of sinful estrangement from and gracious reconciliation in God, Weaver shows how individuals negotiate their relationships with God in and through their involvement with others and the world. Much of current Christian ethics focuses more on persons and their virtues and vices exemplified by the work of vir.